Does Book Subject Influence Format Preference? Survey Results From a Sample of Graduate Business School Students, Staff, and Faculty - Costello, Bethany Koestner (Journal of business & finance librarianship, 2014)
A sample of 325 students, faculty, and staff at a graduate business school completed an online survey designed to assess their knowledge and utilization of the library's e-book collection as well as their desired method of accessing various types of books. Participants were asked about their format preference for reading four different types of books: course textbooks, computer software guides, career development books, and popular business titles. The final section of the survey gave respondents an opportunity to provide free form comments and thoughts about e-books. The implications of this research for collection development are discussed.